Cuidados posoperatorio inmediato de enfermería en pacientes diabéticos con amputación de miembros inferiores: revisión sistemática - Altamirano García, Cindy Yaritza (2026)
Introduction: Nursing care can be defined as the method by which professionals carry out appropriate and safe interventions, especially in the postoperative period following surgical amputations related to Diabetes Mellitus. Objective: To identify immediate postoperative nursing care in diabetic patients with lower limb amputations through a systematic review. Methodology: The study was based on a meticulous review of scientific databases such as PubMed, Scopus, SciELO, and ScienceDirect, as well as university repositories. Articles containing information on postoperative nursing care and surgical lower limb amputation in diabetic patients were located. This information was systematically collected by selecting articles from the last four years that met the selection criteria. The PRISMA methodology was applied; Initially, 80 articles were reviewed; ultimately, 20 met the required scientific standards. Results: The evidence on surgical lower limb amputations highlighted that supracondylar amputations are the most frequent, and the most associated factors include being male, having high blood glucose, infections, and inadequate control during treatment. Similarly, 8 studies were related to postoperative nursing care, with mental health care and education for both the patient and caregiver being the most recurring topics. Conclusion: Nursing care is fundamental, enabling patients to adjust to their new health status after amputation, as well as providing a range of care that promotes the recovery process.